User Experience Analysis of Mobile Banking in Indonesia: Usability Testing & UEQ Case Study of Bank Jago Syariah - Aprilia Puspitasari; Adela Ika Febiyanti; Lanjar Dian Pramesti; Mareta Galus Prastiti (Presscience, 2025)
This study aims to evaluate the user experience of mobile banking applications in Indonesia using usability testing and the User Experience Questionnaire (UEQ). Given the rapid growth of mobile banking technology, significant attention must be paid to user experience to ensure the application is efficient and enjoyable. By combining these two research approaches, we identify key factors influencing user experience, such as user interface, navigation, and overall satisfaction. Usability testing was conducted to assess how well the mobile banking application meets user needs and expectations. Participants completed a series of tasks designed to cover the application's main features, while researchers observed and recorded responses, challenges, and time spent on each task. The results provided valuable insights into specific issues users face while interacting with the app. Following this, the UEQ was used to measure qualitative aspects of the user experience, including satisfaction, anxiety, stimulation, and focus. Users filled out the questionnaire after interacting with the app, providing data on their perceptions and emotions during usage. The UEQ data helped identify design elements that positively or negatively impact user experience. The findings offer a deep understanding of the strengths and weaknesses of mobile banking applications in Indonesia. This information can guide developers in making necessary improvements to ensure users have a satisfying and efficient experience. The research also contributes to raising awareness and understanding of user-centered mobile banking application development in Indonesia.